mTOR-Activating mutations in RRAGD are causative for kidney tubulopathy and cardiomyopathy - (:unkn) unknown (American Society of Nephrology, 2021)
Background Over the last decade, advances in genetic techniques have resulted in the identification of rare hereditary disorders of renal magnesium and salt handling. Nevertheless, approximately 20% of all tubulopathy patients lack a genetic diagnosis. Methods We performed whole-exome and genome sequencings of a patient cohort with a novel inherited salt-losing tubulopathy, hypomagnesemia, and dilated cardiomyopathy. We also conducted subsequent functional analyses in vitro of identified variants of RRAGD, a gene that encodes a small Rag guanosine triphosphatase (GTPase). Results In eight children from unrelated families with a tubulopathy characterized by hypomagnesemia, hypokalemia, salt wasting, and nephrocalcinosis, we identified heterozygous missense variants in RRAGD that mostly occurred de novo. Six of these patients also had dilated cardiomyopathy and three underwent heart transplantation. We identified a heterozygous variant in RRAGD that segregated with the phenotype in eight members of a large family with similar kidney manifestations. The GTPase RagD encoded by RRAGD plays a role in mediating amino acid signaling to the mechanistic target of rapamycin complex 1 (mTORC1). RagD expression along the mammalian nephron included the thick ascending limb and the distal convoluted tubule. The identified RRAGD variants were shown to induce a constitutive activation of mTOR signaling in vitro. Conclusions Our findings establish a novel disease, which we call autosomal dominant kidney hypomagnesemia (ADKH-RRAGD), that combines an electrolyte-losing tubulopathy and dilated cardiomyopathy. The condition is caused by variants in the RRAGD gene, which encodes Rag GTPase D; these variants lead to an activation of mTOR signaling, suggesting a critical role of Rag GTPase D for renal electrolyte handling and cardiac function. Copyright © 2021 by ASN, Published Ahead of Print on 10/4/21, Accepted/Unedited Version
Keywords: Hypomagnesemia; MTOR; Nephrocalcinosis; Rag complex